Synonymy and biogeography of the dinoflagellate genus Histioneis (Dinophysiales: Dinophyceae) - Gómez, Fernando (2007)
The genus Histioneis (=Parahistioneis) contains an excessive number of poorly described species, often based on the observation of a single specimen and ignoring the intraspecific variability. In order to investigate the validity of the species and to suggest synonyms, the original illustrations of all known species of Histioneis are reproduced and grouped based on the morphological similarity. The scarce records and the uncertainties on the identification at the species level are responsible of the lack of biogeographical information. Large and highly ornamented species tended to appear in tropical waters, whereas smaller and less ornamented species showed a wider distribution and they can also found in temperate waters such as the Mediterranean Sea.